Occurrence and Predictors of Diabetes Distress in Adult Patients with Type 2 Diabetes from North India - Joshita Gupta; Deepak Khandelwal; Lovely Gupta; Deep Dutta; Suresh Mittal; Ritesh Khandelwal; Sachin Chittawar (Indian Journal of Endocrinology and Metabolism)
Introduction: There is limited data regarding the prevalence and predictors of diabetes distress in Indians with type 2 diabetes (T2D). The study aimed to determine the occurrence and predictors of diabetes distress in adult persons with T2D. Methods: In a cross-sectional study, persons with T2D on pharmacotherapy for at least 1 year were evaluated. They were administered three questionnaires namely- Diabetes Distress Scale-17, Patient Health Questionnaire-9, and Morisky Medication Adherence Scale-8. Clinically meaningful data regarding diabetes complications, anthropometry, and biochemical parameters were recorded. Results: Two hundred persons completed the study (mean age 57 ± 9.89 years, 59% males). Overall 140 (70%) of the patients had diabetes distress (mean DDS score ≥2). Clinically significant diabetes distress (CSDD) that requires a physician’s attention (mean DDS score ≥3) was seen in 75 (37.50%) of the study participants. The mean HbA1c was significantly higher in participants with CSDD (10.24 ± 2.01 vs. 7.85 ± 1.14; P = <0.001). Both microvascular [retinopathy (28% vs. 5.60%; P ≤ 0.001), neuropathy (28% vs. 0%; P ≤ 0.001), nephropathy (32% vs. 6.40%; P ≤ 0.001)] and macrovascular (CAD 24% vs. 4.80%; P ≤ 0.001) and (CVA 6.67% vs. 1.60%; P = 0.059) complications were significantly correlated with CSDD. Medication adherence was significantly lower in patients with CSDD (p=<0.001). An increased number of insulin injections increased BMI and HbA1c, and the presence of nephropathy were independent predictors of CSDD. Conclusion: Diabetes distress is a common co-morbid condition in persons with T2D. CSDD had a significant correlation with poor glycaemic control, higher BMI, presence of nephropathy, and higher number of insulin injections.